2007
DOI: 10.1007/s11434-007-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal freeze/thaw cycles of the ground surface on the Tibetan Plateau

Abstract: The exchange of energy and water between the lithosphere and atmosphere mainly takes place at the ground surface. Therefore, freeze/thaw condition at the ground surface is an important factor in examining the interactions between the land surface and atmosphere. Based on the observation data obtained by CEOP/CAMP-Tibet, the diurnal freeze/thaw cycles of the ground surface near Naqu, central Tibetan Plateau was preliminarily analyzed. The results show that the surface layer was completely frozen for approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 11 publications
1
41
0
2
Order By: Relevance
“…However, the whole permafrost layer below the surface remained in a frozen state. During the months of April and October, frequent positive and negative variations in the daily surface temperature occurred [19]. This coincides with the transition stages for the freeze-thaw transformation of the active permafrost layer.…”
supporting
confidence: 60%
“…However, the whole permafrost layer below the surface remained in a frozen state. During the months of April and October, frequent positive and negative variations in the daily surface temperature occurred [19]. This coincides with the transition stages for the freeze-thaw transformation of the active permafrost layer.…”
supporting
confidence: 60%
“…The yellow band denotes the freezing stage, the green band denotes the thawing stage, the area between the two bands denotes the completely frozen stage, and the outside of them denotes the completely thawed stage. Yang et al (2007) examined the days of the four freeze/thaw stages and found that the time that the surface undergoes diurnal freeze/thaw cycles is approximately 6 months. In this study, an attempt was made to investigate the relationship between sensible and latent heat flux and diurnal variation in soil surface temperature and moisture under four soil freeze/thaw conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The data collected during these projects have been used by many studies investigating the interaction between the land surface and atmosphere (Yang et al 1999a(Yang et al , b, 2003(Yang et al , 2007Ma et al 2004Ma et al 2005;Tanaka et al 2001;Gao et al 2004;Cheng et al 2008;Guo et al 2009a, b). Diurnal variation in sensible and latent heat flux, soil temperature, and soil moisture in different seasons has also been reported (Yu et al 2004;Ma et al 2005Yang et al 1999aYang et al , b, 2003Yang et al , 2007Zhao et al 2007). However, few studies have focused on the relationship between sensible and latent heat flux and diurnal variation in soil surface temperature and moisture over the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…They found an earlier onset date of soil thaw in spring, and determined that the number of frozen days decreased by ~16. Yang et al (2007) investigated the freeze-thaw processes in central Qinghai-Tibetan Plateau based on onestation high-frequency observation from 2003 through 2004. They found that the number of days at the station with a daily minimum temperature below 0 °C was ~230, and the freeze-thaw cycles were of high frequency at the ground surface.…”
Section: Introductionmentioning
confidence: 99%